2017
DOI: 10.1007/jhep01(2017)053
|View full text |Cite
|
Sign up to set email alerts
|

The forward-backward asymmetry for massive bottom quarks at the Z peak at next-to-next-to-leading order QCD

Abstract: We compute the order α 2 s QCD corrections to the b-quark forward-backward asymmetry in e + e − → bb collisions at the Z boson resonance, taking the non-zero mass of the b quark into account. We determine these corrections with respect to both the b-quark axis and the thrust axis definition of the asymmetry. We compute also the distributions of these axes with respect to the electron beam. If one neglects the flavor singlet contributions to the b-quark asymmetry, as was done in previous computations for massle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…The top-quark polarization in tt events is predicted to be very small in the SM [113]; the exact value depends on the choice of the spin quantization axis, as discussed in Section 2. to the central values and uncertainties given in table 1 and table 2. The uncertainties were assumed to be uncorrelated.…”
Section: Top Quark Polarization and Tt Spin Correlationsmentioning
confidence: 97%
See 1 more Smart Citation
“…The top-quark polarization in tt events is predicted to be very small in the SM [113]; the exact value depends on the choice of the spin quantization axis, as discussed in Section 2. to the central values and uncertainties given in table 1 and table 2. The uncertainties were assumed to be uncorrelated.…”
Section: Top Quark Polarization and Tt Spin Correlationsmentioning
confidence: 97%
“…Top quarks and antiquarks produced in tt pair production show only very small polarization (approximately 1%, depending on the initial state and the choice of the quantization axes [113]); however, their spins are significantly correlated. The quantum-mechanical observable connected to a spin is its projection to a quantization axis.…”
Section: Top Quark-antiquark Pair Productionmentioning
confidence: 99%
“…2.1 PMC scale-setting for the b quark pair production cross section in electron-positron collisions For our PMC scale-setting analysis for the b quark forwardbackward asymmetry to NNLO in QCD, we employ the computational set-up of Refs. [11,13] for massive b quark pair production in electron-positron collisions. The NNLO QCD corrections consist of three classes of contributions: (i) the two-loop and 1-loop squared corrections to the two-parton final state (bb); (ii) the one-loop corrections to the threeparton final state (bbg); (iii) the tree level processes with four-parton final states (bbgg, bbqq, bbbb).…”
Section: Pmc Scale-setting For B Quark Forward-backward Asymmetrymentioning
confidence: 99%
“…The b quark forward-backward asymmetry was computed for m b = 0 at NNLO both for the quark axis and the thrust axis definition in Ref. [13], for conventional scale settings. It was found that this result reduces the tension between the measurements and the SM predictions but only slightly to 2.6σ .…”
Section: Introductionmentioning
confidence: 99%
“…The first measurement of APV as a function of isotope number has been achieved by the group of Dima Budker at the JGU Mainz [18] just a few months ago, where the weak charges of Ytterbium showed the expected isotope dependence. Note, that there has been a change in the sin 2 θ W extraction from the FB asymmetry for bb final states by the LEP Collaborations, as two years ago the two-loop QCD correction necessary to extract the pole asymmetry has been obtained with the finite b quark mass dependence [20], reducing the largest LEP discrepancy with the SM by about a quarter of a standard deviation. Another change affected the extraction from the APV measurement in 133 Cs [15], for which the Stark vector transition polarizability needs to be known.…”
Section: Introductionmentioning
confidence: 99%